Accounting Information System of the Seventh-day Adventists Church-owned Secondary Schools in the Philippines - Ruhupatty, LeRoy Tim (JIU (Jurnal Ilmiah Unklab), 2002)
This paper examines the perception of accounting information system (AIS) users in the characteristics of their AIS; its responsiveness to change in information technology (IT), management’s information need, and changes in number of students; and whether its objectives were met. The population of this study is the Seventh-day Adventists Church owned and operated secondary schools in the Philippines. It was found that the schools’ AIS have the characteristics of successful AIS, responsive enough to changes and able to meet its objectives. Furthermore, it was found that there was no significant difference in the characteristics of the schools’ AIS when grouped according to age of school, degree of computerization and manpower size. It was also found that there was no significant correlation between the responsiveness of the schools AIS with age of School, manpower size and budgetary support for the accounting department.